PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITAS, DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013--2015 - Sulistyowati, Sulistyowati; Ulfah, Lisa Ariska (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2018)
Tax Aggressiveness is action taken to minimize the expenses of the taxpayer receives tax payable. The more efficient the tax expenses of State revenues from taxes will also decrease. This study was conducted to determine the effect of Corporate Social Responsibility Disclosure, Profitability and Leverage on Tax Aggressiveness in manufacture firms that listed at Indonesian Stock Exchange for the year 2013 – 2015. The sample was determined by purposive sampling method that listed at Indonesian Stock Exchange for the year of 2013 – 2015, with a total sample of 29 manufacture firms for a total observation in this study a total of 87 observations. The data used in this research is secondary data, in the form of a financial report and annual reports that downloaded via the official Indonesia Stock Exchange’s website. Data were analyzed using pooled data regression that processed using Eviews version 8.0 software. Hypothesis testing using t-statistic test. The results obtained are profitability variable which proxied by return on asset (ROA) had a significant impact on tax aggressiveness. While corporate social responsibility disclosure variable which proxied by corporate social responsibility index (CSRI) and leverage variable had no significant effect on tax aggressiveness.